Kinematic GNSS inversion of the large afterslip (Mw 6.4) following the 2019 Mw 6.2 Hualien earthquake (Taiwan) - Lin, Hsiao-Fan; Canitano, Alexandre; Hsu, Ya-Ju (Frontiers in Earth Science, 2024)
The postseismic deformation following the April 2019 Mw 6.2 Hualien earthquake presents an unique opportunity to investigate the mechanisms by which the northern section of the Longitudinal Valley accommodates lithospheric deformation. We apply a variational Bayesian independent component analysis approach to displacement time-series to infer a 6-month long afterslip. Kinematic inversion shows that displacements are well explained by widespread afterslip (∼60 km in the along-strike direction) with limited slip (≤0.1 m) surrounding the coseismic slip area. The total geodetic moment relieved by afterslip (M0 ∼ 4.6 × 1018 Nm, i. e., Mw ∼ 6.4) is twice as large as the mainshock seismic moment, which represents a rare exception of a moderate magnitude event for which the afterslip moment exceeds that of the seismic moment. Then, combining geodetic and seismological analysis, we infer that afterslip is the dominant mechanism of near-to intermediate-field postseismic deformation and also likely represents the driving force that controls aftershock productivity and the spatiotemporal migration of seismicity. Besides, the fault zone frictional stability parameter a-b of rate-and-state dependent friction (a-b ∼ 0.0067–0.02) is comparable with previous estimates in the Longitudinal Valley. Finally, the study demonstrates that the northern Longitudinal Valley region hosts complex seismogenic structures that display a variety of slip behaviors.